Hubungan Kekerabatan Fenetik Melon Cantaloupe, Honey Globe, Devina, Luna, Sweetnett dan Hamigua Berdasarkan Karakter Kualitatif - Ibnu Fajar, S.Pd., M.Sc, Muhammad; Wiwik Sri Untari; Shinta Nuriya Prayudi (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
This study aims to determine the phenetic relationship of the six melons Cantaloupe, Honey Globe, Devina, Luna, Sweetnett and Hamigua based on quantitative phenotypic characters of melons. Research and research samples were taken and conducted at the Situbondo nugrafarm. The qualitative phenotypic characters observed consisted of 88 characters including root branching, epicotyl color, hypocotyl color, stem color, leaf shape, leaf color, leaf stalk color, flower color, ovary shape, fruit shape, fruit skin color, fruit stalk color, fruit flesh color, fruit flesh texture, fruit flesh taste, seed shape and seed coat color. Qualitative characters were processed into scoring data that were analyzed using MVSP software using the Jaccard Coefficient correlation coefficient. The dendogram was divided into 4 groups with a similarity index of 62%. The results of the study showed that group I, Devina melon is closely related to Luna melon, group III Cantaloupe melon is distantly related to group I, Devina melon and Luna melon, group II, Hamigua melon is closely related to Sweetneet melon, and group IV Honey Globe melon is distantly related to the five melon varieties. The qualitative phenotypic similarity of the six melons will be information for plant breeding. Keywords: Melon, Qualitative Character, Kinship Relationship